DETERMINAN NERACA TRANSAKSI BERJALAN INDONESIA (1994-2009) - Ginting, Selly Aritha (e-Journal Perdagangan Industri dan Moneter, 2013)
This research use time series data from 1994 until 2009. The purpose of this research is to analyze the factors affecting Indonesia Current Account. The methods used in this research are descriptive and quantitative analysis, meanwhile, multiple regression was used as a tool of analysis. The factors affecting Indonesia Current Account are exchange rate, foreign investment, gross national product, and domestic inflation.Exchange rates proved a positive affect on current account, foreign investment affect to current account. On the other hand, gross national income precisely has a negative effect on current account. Domestic inflation also has a negative influential to current account. Meanwhile exchange rate, foreign investment, gross national product, and inflation cause a negative effect simultaneously. Government and stakeholders should keep the exchange rate stability because the exchange rate is the most affecting on international trade. Then government also keep our domestic stability on politics, security, economic to increase economic productivity.Keywords: current account, exchange rate, foreign investment, gross national product, inflation REFERENCES Haryadi. 2007. Buku I Ekonomi Internasional Teori dan Kebijakan. Bogor: Biografika.Hamli, Lukman. 2005. Faktor-faktor yang Mempengaruhi Keseimbangan Neraca Pembayaran Indonesia Suatu Pendekatan Moneter (1990-2002). Skripsi.Jambi: Fakultas Ekonomi Universitas Jambi.Krugman, Paul R dan Maurice Obstfeld. 2005. Ekonomi Internasional Teori dan Kebijakan. Jakarta: Rajawali Press.Sukirno, Sadono. 1996. Pengantar Teori Makro Ekonomi. Jakarta: Raja Grafindo.Tan, Syamsurijal. 2004. Ekonomi Internasional. Jambi: Pratama.Tambunan, Tulus. 2005. Perekonomian Indonesia, Beberapa Masalah Penting. Jakarta: Ghalia Indonesia.Todaro, Michael. 1998. Pembangunan Ekonomi di Dunia Ketiga. Jakarta: Erlangga.